Central and South-East European Resources in META-SHARE - Váradi, Tamás (Array, 2012)
The purpose of this demo is to introduce the Language Resources, Tools and Services (LRTS) that are being prepared within the Central and South-East European Resources (CESAR) project. To the computational linguistic community the languages covered by CESAR (Bulgarian, Croatian, Hungarian, Polish, Serbian and Slovakian) were so far considered under-resourced and their language resources and tools being insufficient or hard to obtain, with limited coverage and processing capabilities. The CESAR project, functioning as an integral part of META-NET initiative, aims to change this situation by coordinating all relevant national stakeholders, to enlarge and enhance the existing LRTSs, as well as connect them multi-lingually in various ways. The most important aim of the project is to make all LRTSs for respective languages accessible on-line through the common European LRTS distribution platform META-SHARE. This demo will present how this platform can be used in different scenarios and how researchers or industry partners can easily access CESAR Language Resources, Tools and Services.